Upaya Meningkatkan Hasil Belajar Tendangan Pencak Silat pada Siswa Kelas V-A SDN Bubutan IV Surabaya Tahun Pelajaran 2024/2025 Melalui Modifikasi Pembelajaran Hanging Ball - Abdul Rohman; Advendi Kristiandaru; Rinda Kuswati (Jurnal Kajian dan Penelitian Umum, 2024)
This research aims to improve the learning outcomes of pencak silat kicks for class V-A students at SDN Bubutan IV Surabaya through learning modifications using a hanging ball. This classroom action research was carried out in two cycles, each consisting of planning, action, observation and reflection stages. In the pre-cycle, only 40% of students achieved completeness, of which 12 students were declared complete. After the first intervention using the Shadow Fighting method, the percentage of completion increased to 67% where 20 students were declared complete, but not yet satisfactory. In the second cycle, the use of a hanging ball increased completion to 87%, of which 26 were completed out of 30 students. These results show that hanging balls are effective in making learning more dynamic, interesting, and increasing student motivation. This modification not only improves kicking skills, but also strengthens students' understanding of basic pencak silat movements, creating a higher quality learning process.